2008
DOI: 10.1038/bmt.2008.394
|View full text |Cite
|
Sign up to set email alerts
|

Prior immunosuppressive therapy with antithymocyte globulin increases the risk of EBV-related lymphoproliferative disorder following allo-SCT for acquired aplastic anaemia

Abstract: We reviewed the incidence and risk factors for EBVrelated post-transplant lymphoproliferative disorder (EBV-PTLD) in 89 patients with acquired aplastic anaemia (AAA) receiving allogeneic transplants between 1989 and 2006. The overall incidence of EBV-PTLD was 6.3% (5/89) with no cases in those receiving an allograft for constitutional BM failure syndromes (n ¼ 30) during the same period. There was no impact of age, gender, donor status, CMV seropositivity, GVHD and graft cell dose on the occurrence of PTLD. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 9 publications
0
32
1
Order By: Relevance
“…We have previously shown that there is a strong association of EBV PTLD post-HSCT for SAA when ATG is used as IST for AA before HSCT. 22 We observed no expansion of PNH clones post-HSCT. Lymphocytes deficient in the expression of GPI-anchored proteins may emerge after treatment with alemtuzumab, mimicking a PNH clone, as a result of immune selection by the anti-CD52 Ab.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We have previously shown that there is a strong association of EBV PTLD post-HSCT for SAA when ATG is used as IST for AA before HSCT. 22 We observed no expansion of PNH clones post-HSCT. Lymphocytes deficient in the expression of GPI-anchored proteins may emerge after treatment with alemtuzumab, mimicking a PNH clone, as a result of immune selection by the anti-CD52 Ab.…”
Section: Discussionmentioning
confidence: 73%
“…The high survival of early patients with early graft failure was in part because of a high incidence of autologous recovery, in ϳ 50% of patients. 19,22 We previously used alemtuzumab with fludarabine-based conditioning for UD HSCT and reported excellent engraftment in a small series of patients with both acquired and inherited SAA. 21 Risk factors for chronic GVHD after HSCT for SAA include acute GVHD, older age, and donor chimerism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Published experience regarding the incidence of EBV-PTLD after allogeneic HCT ranges between 0.5 and 17% and is mainly based on single-centre experiences or retrospective studies limited by small numbers and diverse patient characteristics. [4][5][6][7] However, Landgren et al 8 collected data on 127 EBV-PTLD cases from 271 centres and found an elevated risk for developing PTLD especially in the first year after HCT (83%) with the highest occurrence during the first 6 months. However, late EBV-PTLD could be observed even up to 10 years after HCT.…”
Section: Introductionmentioning
confidence: 99%
“…Buyck et al (2009) reported that the overall incidence of EBV-PTLD in patients with acquired aplastic anemia receiving allotransplants was 6.3%, and prior use of ATG strongly influenced the development of PTLD; in particular, those receiving multiple prior courses of ATG were at the highest risk. Presumably the reason is that T-cell dysfunction caused by multiple courses of ATG might create a unique environment for EBV replication.…”
Section: Discussionmentioning
confidence: 99%